(untitled) (Research, Society and Development, 2020)
In the Amazon, research and public policies supporting Urban and Periuirban Agriculture (AUP in Portuguese) are still in their initial stages, therefore, lacking incentives to contribute with rapid urbanization problems occurring in the region, specially unemployment, poverty and food insecurity. This research sought to identify the socioeconomic profile and productive dynamics of AUP systems adopted in the Municipality of Irituia, State of Pará, as a means to subsidize the local development strategy, especially those related to food security and labor occupation in urban and periurban areas of Amazon cities. It was used the quantitative and qualitative methodological approach through 40 semi-structured questionnaires applied to urban and periurban farmers of the municipality. It was possible to identify three distinctive farmers categories: a) farmers that developed the activity as the main income source (42.5%); b) public servants who worked in agriculture to complement their income (32.5%); and, c) small traders who worked in agriculture at the same time as in their business activities (25.0%). Even though it had been evidenced no effective public policy to foster AUP in Irituia, it is noticeable the spontaneous initiative across the municipality due to its rural nature, as well as a significant growth potential in the activity. The results found are relevant to plan concrete actions in order to foster the activity and the urban and periurban development of Irituia Municipality.